Paradoks Sentralisasi dalam Desentralisasi: Analisis Konflik Norma Vertikal-Horizontal pada Evolusi UU Pemerintahan Daerah di Indonesia - Desi Ayuherma Anugrah; I Dewa Gede Herman Yudiawan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study analyzes normative conflicts in the evolution of local government regulations from Law No. 22 of 1999 to Law No. 23 of 2014, along with the changes following the Job Creation Law. The research background is grounded in the phenomenon of policy pendulum swings, which indicate a shift from radical decentralization toward structured centralization, as well as the disruptions caused by the omnibus law approach. The research aims to identify and classify vertical and horizontal normative conflicts and formulate recommendations for regulatory harmonization. The method used is normative legal research with a legislative and conceptual approach, employing Hans Kelsen’s theory of antinomy as an analytical tool. The research findings identified two main forms of normative conflict: first, a vertical conflict between Law No. 22/1999, which advocates for the broadest possible autonomy, and Law No. 23/2014, which strengthens central control through the concepts of absolute affairs and NSPK, creating a paradox of centralization within decentralization. Second, a horizontal conflict following the Job Creation Law, which centralizes regional licensing authority through the OSS system and revives Article 251 regarding the annulment of regional regulations that have been declared unconstitutional by the Constitutional Court. The implications of this research recommend revising problematic articles and strengthening the role of regions within a just decentralization system.